(untitled) (Latin American Journal of Sedimentology and Basin Analysis, 2021)
Starting with present issue, the new Latin American Journal of Sedimentology and Basin Analysis (LAJSBA) is born. This was announced by Matheos and Perillo (2204) as way to expand the future and to achieve a larger integration among the Latin American researchers. During the last 11 years, AAS Revista was the main way to express our scientific views but mostly concentrated in the work being done in Argentina. LAJSBA has arrived to provide a complete new spectrum of possibilities reaching also a much larger international community. However, we do not see LAJSBA as circumscribed to papers written by Latin American researchers but it is open to any specialist that would like to contribute to enhance our knowledge about Sedimentology and Basin Analysis.